The Role of Social Learning in Instilling Multicultural Values Towards the 6th Graders Students of SD Negeri 01Kragan - Hunatali, Pristya Dinambar; Tri Atmaja, Hamdan; Hartono, Hartno (Educational Management, 2021)
The purpose of this research was to analyzed the role of social study (IPS) in Embedding multicultural values in sixth grade students at Kragan 01 primary school. This Study used qualitative research method. Data collected by interview, obsevation, and documentation. The data validity techique used the trianggulation method. The data analysis technique used interactive model of miles and huberman. The focus of research examinined the role of social studies learning in multicultural values. The result showed that the role of social studies learning in embedding multicultural education were : (1) embedding values and attitudes of tolerance, mutual undertanding, openness, inclusivism for diversity (2) Children had knowledge about cultural diversity and social problem (3) Built anti-discrimination and equality attitudes. The implication of the results of this study was embedding multicultural values was very useful for unifying the nation and reducing conflict.